Earnings Management and Tax Minimization: Comprehensive Analysis of Book-Tax Differences in Indonesia - Hashfi, Muhammad Hammam Al; Martani, Dwi (Jurnal Kajian Akuntansi, 2023)
The research aims to investigate the relationship between earnings management strategies, specifically Accrual Earnings Management (AEM) and Real Earnings Management (REM), and abnormal book-tax differences (ABTD). A quantitative approach was employed, utilizing multiple regression models, descriptive statistics, model testing, classical assumption testing, and hypothesis testing through Eviews 12 software on a sample of 671 observations from 61 companies listed on the IDX from 2011 to 2021. The results reveal a significant positive relationship between ABTD and both AEM and REM through overproduction. However, no significant relationship was found between REM and abnormal operating cash flow. Interestingly, a strong negative correlation was discovered between tax avoidance and earnings management through discretionary spending. These findings suggest that accrual management practices are associated with higher levels of tax avoidance, while discretionary spending for earnings management tends to decrease it. The implications of this study provide insights into potential earnings management techniques that can enhance corporate efforts to reduce tax payments and maximize profits while serving as a warning for potential tax avoidance activities.